The political economy of poverty in Egypt (1975-2000): a sociological perspective - Ibrahim, Mohammed Abdel Hamid (Islam and Christian-Muslim relations, 2004)
Studies of poverty in the 1990s have been very successful--more successful than the fight against the phenomenon itself. Had the efforts exerted to combat poverty equalled the concern given to the study of the problem, the poor would have enjoyed better conditions and the level of poverty would have diminished locally and worldwide. The current study identifies the relation between impoverishment, marginalization of particular groups in society and the nature of the political, economic and social policies adopted by the state in Egypt, in one of the important stages of social structure formation in the country--1975-2000. These policies play a direct role in creating the mechanisms of impoverishment and marginalization in Egyptian society, leading naturally to producing and reproducing poverty.